(untitled) (Architecture Image Studies, 2025)
The study aims to empirically investigate the relationships among lean production practices, business performance, and operational performance within the Malaysian manufacturing firms. Anchored in Socio-Technical Systems Theory (STS) and Program Theory, the study develops and tests a conceptual framework that distinguishes between socially-oriented lean production (SLEAN) and technically-oriented lean production (TLEAN), examining their individual and combined effects on BP and OP outcomes. While existing theoretical frameworks suggest a positive relationship between lean practices and organizational performance, prior empirical findings have been mixed and, in some cases, inconclusive. Addressing this gap, the present study employs sample data of 205 manufacturing firms, selected randomly from the Federation of Malaysian Manufacturers Directory. Structural Equation Modeling (SEM) was conducted to analyze the data using the AMOS and SPSS software programs. The findings show that lean approaches that are both technically and socially oriented have significantly improved the OP. Furthermore, the OP is found to partially mediate the relationship between both dimensions of BP and lean production. A significant direct relationship is also observed between BP and OP. This study contributes to the operations management literature by providing empirical validation of the differentiated roles of social and technical lean practices in shaping firm-level performance. The findings offer both theoretical and practical implications, improving the academic discourse on lean production systems and offering actionable insights for managers seeking to implement and sustain lean initiatives to enhance organizational outcomes.